Investigation of PPARβ/δ within Human Dental Pulp Cells: A Preliminary In Vitro Study - Caroline L. de Lima; Bruna R. Amorim; Carine Royer; Augusto P. Resende; Maria F. Borin; Francisco A. R. Neves; Ana Carolina Acevedo (PPAR Research)
Controlling the inflammatory response to restore tissue homeostasis is a crucial step to maintain tooth vitality after pathogen removal from caries-affected dental tissues. The nuclear peroxisome proliferator-activated receptor beta/delta (PPARβ/δ) is a ligand-activated transcription factor with emerging anti-inflammatory roles in many cells and tissues. However, its expression and functions are poorly understood in human dental pulp cells (hDPCs). Thus, this study evaluated PPARβ/δ expression and assessed the anti-inflammatory effects evoked by activation of PPARβ/δ in lipopolysaccharide- (LPS-) induced hDPCs. Our results showed that hDPCs constitutively expressed PPARβ/δ mRNA/protein, and treatment with LPS increased PPARβ/δ mRNA expression. The selective PPARβ/δ agonist GW0742 significantly decreased inflammation-related mRNA expression in hDPCs (IL6, IL1β, TNFα, MMP1, and MMP2) and RAW264.7 cells (Il6 and Tnfα). Further, PPARβ/δ agonist attenuated MMP2/9 gelatinolytic activity in hDPCs. Previously LPS-conditioned hDPCs increased the migration of RAW264.7 cells through the membrane of a Transwell coculture system. Conversely, pretreatment with GW0742 markedly decreased macrophage recruitment. These findings provide among the first evidence that hDPCs express PPARβ/δ. In addition, they suggest that activation of PPARβ/δ by GW0742 can attenuate some cellular and molecular in vitro aspects related to the inflammatory process, pointing out to investigate its potential target role in dental pulp inflammation.